The Development of Dengue Hemorrhagic Fever Cases in Majene Regency, West Sulawesi Province Period 2022–2024 - Zahwa Nizar; Siti Selfia (Journal of Epidemiology and Health Science, 2025)
Background: Dengue Hemorrhagic Fever (DHF) is a major infectious disease and a significant public health concern in tropical regions, including Indonesia. In the country, DHF incidence fluctuates annually, with a tendency toward increased morbidity and geographic expansion of affected areas. Extraordinary DHF outbreaks occur almost every year in different locations and are difficult to predict. In West Sulawesi Province, the morbidity rate is 39.25 per 100,000 population and the case fatality rate (CFR) is 1.13—both exceeding the national average. Majene Regency has reported the highest DHF cases in recent years, with 202 cases recorded in 2023. Objective: This study aims to analyze the trend and distribution of DHF cases in Majene Regency during 2022–2024 based on secondary data from the Majene Regency Central Statistics Agency. Methods: This research applied a quantitative descriptive method using secondary data obtained from the Central Statistics Agency (BPS) of Majene Regency. Data were presented in tables and graphs to illustrate temporal and spatial trends and were narratively interpreted to identify patterns. Results: The findings indicate a marked increase in DHF cases from 2022 to 2024, with the highest incidence in 2024, particularly in Pamboang and Sendana Districts. Key contributing factors include climate change, high population density, and inadequate environmental sanitation. Conclusion: The upward trend of DHF in Majene Regency underscores the urgent need for collaborative efforts between government and communities to enhance public awareness and implement sustainable mosquito breeding site eradication programs. Keywords: Dengue Hemorrhagic Fever, climate change, sanitation, morbidity, population density, Indonesia